(untitled) (Scientific journal of the Fergana State University, 2024)
In certain areas of Uzbekistan, the problem of swamping is observed. This issue is particularly noticeable in settlements located in saline soils. This article discusses the damage caused by the swamping of some cities located in the low relief of the Syrdarya region of the Republic of Uzbekistan. Deficiencies in drainage during irrigation lead to a rise in groundwater levels, swamping, and significant damage to buildings and structures. Through social surveys, the material damage caused to the populations of affected cities due to swamping was assessed. The results showed that nearly 60 percent of the population is forced to carry out additional repairs on their homes annually due to swamping and salinization. On average, this amounts to 322.4 dollars per household per year, which is nearly equivalent to the average monthly wage.